Failure to decrease HbA1c levels following TB treatment is associated with elevated Th1/Th17 CD4+ responses - Krause, Robert; Warren, Christian M.; Simmons, Joshua D.; Rebeiro, Peter F.; Maruri, Fernanda; Karim, Farina; Sterling, Timothy R.; Koethe, John R.; Leslie, Al; van der Heijden, Yuri F. (Frontiers in Immunology, 2023)
The rising global burden of metabolic disease impacts the control of endemic tuberculosis (TB) in many regions, as persons with diabetes mellitus (DM) are up to three times more likely to develop active TB than those without DM. Active TB can also promote glucose intolerance during both acute infection and over a longer term, potentially driven by aspects of the immune response. Identifying patients likely to have persistent hyperglycemia following TB treatment would enable closer monitoring and care, and an improved understanding of underlying immunometabolic dysregulation. We measured the relationship of plasma cytokine levels, T cell phenotypes and functional responses with the change in hemoglobin A1c (HbA1c) before and after treatment of pulmonary TB in a prospective observational cohort in Durban, South Africa. Participants were stratified based on stable/increased HbA1c (n = 16) versus decreased HbA1c (n = 46) levels from treatment initiation to 12 month follow-up. CD62 P-selectin was significantly upregulated (1.5-fold) and IL-10 downregulated (0.85-fold) in plasma from individuals whose HbA1c remained stable/increased following TB treatment. This was accompanied by increased pro-inflammatory TB-specific IL-17 production (Th17). In addition, Th1 responses were upregulated in this group, including TNF- production and CX3CR1 expression, with decreased IL-4 and IL-13 production. Finally, the TNF-+ IFNγ+ CD8+ T cells were associated with stable/increased HbA1c. These changes were all significantly different in the stable/increased HbA1c relative to the decreased HbA1c group. Overall, these data suggest that patients with stable/increased HbA1c had an increased pro-inflammatory state. Persistent inflammation and elevated T cell activity in individuals with unresolved dysglycemia following TB treatment may indicate failure to fully resolve infection or may promote persistent dysglycemia in these individuals, and further studies are needed to explore potential mechanisms.